Precise null-pointer analysis using Global Value Numbering - Das, Ankush; Lal, Akash (Automated Technology for Verification and Analysis (ATVA), 2017)
Precise analysis of pointer information plays an important role in many static analysis tools. The precision, however, must be balanced against the scalability of the analysis. This paper focusses on improving the precision of standard context and flow insensitive alias analysis algorithms at a low scalability cost. In particular, we present a semantics-preserving program transformation that drastically improves the precision of existing analyses when deciding if a pointer can alias null. Our program transformation is based on Global Value Numbering, a scheme inspired from compiler optimization literature. It allows even a flow-insensitive analysis to make use of branch conditions such as checking if a pointer is null and gain precision. We perform experiments on real-world code and show that the transformation improves precision (in terms of the number of dereferences proved safe) from 86.56% to 98.05%, while incurring a small overhead in the running time.